Managerial Leadership Principal of Senior High School: Case Studies in SMAN 2 Bandar Lampung, Indonesia - Sowiyah, Sowiyah; Perdana, Ryzal; Baehaki, Farhan (Jurnal Pendidikan Progresif, 2021)
Managerial Leadership Principal of Senior High School: Case Studies in SMAN 2 Bandar Lampung, Indonesia. Objective: This study aims to analyze and describe the managerial leadership of the Principal of State Senior High School 2 Bandar Lampung, Indonesia. Methods: This research uses a matching method with quantitative and qualitative approaches. The research was conducted at State Senior High School 2 Bandar Lampung with the number of respondents as many as 60 teachers in the school environment. Findings: Data obtained through field observations, questionnaires and supported by interviews and documentation. The results show that (1) principal managerial leadership in conceptual skills involves teacher participation in order to create an effective school, (2) there is a synergy of a harmonious relationship between leaders and teachers in realizing school achievement, and (3) mapping the development of leadership techniques skills for principals. and the acceleration of the residence period of students and an increase in the quality of the master program in educational management.Keywords: effective school management, teachers, quality of school.DOI: http://dx.doi.org/10.23960/jpp.v11.i3.202120